Optimalisasi Isolasi Patchouli Alkohol Dari Minyak Nilam (Patchouli Oil) Dengan Metode Distilasi Vakum - M. Yunus; Munawar Munawar; Haris Z.A (Politeknik Negeri Lhokseumawe, 2021)
This study aims to isolate the alcoholic patchouli from patchouli oil using a vacuum distillation method using vacuum distillation unit. The isolation process is conducted by varying vacuum pressure, distillate volume, and remaining residue volume. The vacuum pressure variated at 1, 1,5, 2, and 2,5 mmHg, distillate volume by 70, 80, and 90 ml, while remaining residue volume at 10, 20, and 30 ml. Samples were analyzed using GC-MS to determine the concentration of patchouli alcohol and analyzed using a pycnometer to determine its density. The results showed that the use of low pressure affected separating patchouli alcohol from patchouli oil. The highest patchouli alcohol content from the isolation results is 100% obtained in 10 ml of remaining residue volume at a pressure of 2 mmHg. This vacuum distillation method is quite effective.